Karyotype analysis of four Vicia species using in situ hybridization with repetitive sequences - Navrátilová, Alice; Neumann, Pavel; Macas, Jirí (Annals of botany, 2003)
Mitotic chromosomes of four Vicia species (V. sativa, V. grandiflora, V. pannonica and V. narbonensis) were subjected to in situ hybridization with probes derived from conserved plant repetitive DNA sequences (18S-25S and 5S rDNA, telomeres) and genus-specific satellite repeats (VicTR-A and VicTR-B). Numbers and positions of hybridization signals provided cytogenetic landmarks suitable for unambiguous identification of all chromosomes, and establishment of the karyotypes. The VicTR-A and -B sequences, in particular, produced highly informative banding patterns that alone were sufficient for discrimination of all chromosomes. However, these patterns were not conserved among species and thus could not be employed for identification of homologous chromosomes. This fact, together with observed variations in positions and numbers of rDNA loci, suggests considerable divergence between karyotypes of the species studied.
Keywords: tandemové repetitivní sekvence; buněčné dělení; RNA ribozomální; ribozomální DNA; Repetitive Sequences, Nucleic Acid; DNA, Ribosomal; karyotypizace; Genome, Plant; Vicia sativa; Karyotyping; Tandem Repeat Sequences; repetitivní sekvence nukleových kyselin; RNA, Ribosomal; Primed In Situ Labeling; vikev; konzervovaná sekvence; Vicia; hybridizace in situ fluorescenční; genetické markery; In Situ Hybridization, Fluorescence; in situ značení DNA s primerem; Cell Division; genom rostlinný; Conserved Sequence; Genetic Markers